PERAN PERCEIVED VALUE MEMEDIASI E-SERVICE QUALITY TERHADAP E-LOYALTY - Kameswari, Ni Putu Vanissa; Rahyuda, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023, 2023)
Technological developments provide many changes in various aspects of business, especially the development of internet technology. Internet developments make every company adjust its marketing strategy by entering the online system to sell its products. The e-commerce model that is experiencing rapid development in Indonesia is Shopee. The purpose of this study is to examine the effect of e-service quality on e-loyalty through perceived value to Shopee e-commerce consumers. The number of samples taken is 110 for Shopee e-commerce consumers. Data were collected through the distribution of questionnaires. The analytical technique used is the Sobel test using path analysis and the VAF test. Based on the results of the analysis, it was found that the e-service quality variable has a positive and significant effect on e-loyalty on Shopee e-commerce consumers, the e-service quality variable has a positive and significant effect on perceived value on Shopee e-commerce consumers, the perceived value variable has a positive and significant impact significantly to e-loyalty to Shopee e-commerce consumers, and the perceived value variable significantly mediates the relationship of e-service quality to e-loyalty to Shopee e-commerce consumers .